Treating intracranial dural arteriovenous fistulas with gamma knife radiosurgery: A single-center experience - Guan-Chyuan Wang; Kuan-Pin Chen; Tsung-Lang Chiu; Chain-Fa Su (Tzu Chi Medical Journal)
Objective: We evaluated the effectiveness and safety of gamma knife radiosurgery (GKRS) for the treatment of intracranial dural arteriovenous fistulas (dural AVFs) over the past 10 years. Materials and Methods: The records of 21 patients diagnosed with dural AVFs between 2004 and 2014 and treated with GKRS were reviewed retrospectively. Complete obliteration (CO) was defined as total symptom relief plus confirmation through magnetic resonance imaging or conventional angiography. Results: The median follow-up was 70.5 months (range 3–136 months). Five patients underwent embolization (2 after GKRS). One patient underwent GKRS twice. The CO rate was 47%, and partial to CO rate was 88%. The complete symptom resolution rate was 77%, and all patients achieved partial to complete symptom resolution. The CO rates for Borden Type I and Type II/III dural AVFs were 66.7% and 25% (P = 0.153), respectively, and complete symptom-free rates were 76.9% and 75.0% (P = 1.000%), respectively. The median duration between initial GKRS and complete symptom resolution was 14.3 months. The median treatment to image-free durations for Borden Type I and Type II/III dural AVFs were 25.9 and 60.4 months (P = 0.028), respectively, and treatment to symptom-free durations were 10.6 and 36.7 months (P = 0.103), respectively. One patient had a recurrent hemorrhage. Two patients experienced brain edema after stereotactic radiosurgery and one patient experienced cystic formation after GKRS. The morbidity rate was 19% (four patients) and there was no mortality. Conclusion: Treatment with GKRS for dural AVFs offers a favorable rate of obliteration. Patients with dural AVFs that are refractory or not amenable to endovascular or surgical therapy may be safely and effectively treated using GKRS.